Estudio de diseño conceptual de un esquema de gasificación de tallos de café en el contexto de una biorefinería. (2022)
Gasification in a thermochemical process in which a material rich in carbon, such as plastics, coal and biomass, which is the material where this project focuses specifically on coffee stems, is transformed through thermochemical reactions into a gas fuel of considerable calorific value that can be used in the production of hydrogen or production of electrical energy through its use in adapted turbines or in internal combustion engines